(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
By means of the decision of 11th December 2020, the Austrian Constitutional Court ruled § 78 StGB, II sentence unconstitutional, in that it absolutely bars medical assistance in dying. According to the Constitutional Court, the right to self-determination encompasses the faculty to decide in autonomy when and how to terminate life free from interferences by State authorities. In the essay I briefly compare this decision with the principles expressed by the Italian and German Constitutional Courts in their case-law.